Impact of offensive-reward rules on young basketball players` performance during small-sided games - Abade, E.; Figueira, B.; Coutinho, D.; Folgado, H.; Moreira, C.; Gonçalves, B. (PLOS ONE, 2024)
This study aimed to investigate the impact of different offensive-reward-related rules on the physical performance, perceived exertion and enjoyment of young basketball players during small-sided games (SSG). Eighteen youth male players (age: 13.3±0.9y; height: 167.0±13.1cm; weight: 50.6±11.5kg; years of practice: 3.1±1.2y) participated in three distinct 3x3 SSG (14x15m pitch) experimental conditions: i) 3x3NORMAL, regular 3x3 game; ii) 3x3POINT-POSS, where the team in possession was rewarded a new ball possession after scoring; iii) 3x3PASSES, where the score was determined by the number of passes made before converting a basket. Players` performance was measured using global positioning systems, rating of perceived exertion and the Physical Activity Enjoyment Scale. Players covered more distance for total (p< .001), low (p< .01) and moderate-speed distance (p< .05), and presented a higher game pace (p< .001) during the 3x3POINT-POSS than in the other conditions. A higher number of accelerations (1-1.99 m·s-2, p < .01) and decelerations (>2 m·s-2, p < .01) were also reported in the 3x3POINT-POSS. Despite the higher external load in the 3x3POINT-POSS, players reported higher perceived exertion during the 3x3PASSES (small to moderate effects). In addition, players reported the 3x3POINT-POSS as being more enjoyfull than the 3x3NORMAL. In conclusion, coaches may consider incorporating the 3x3POINT-POSS to enhance players` external load while simultaneously increasing enjoyment and decreasing perceived exertion. Conversely, the 3x3PASSES condition may be useful for promoting adaptive behaviors under a higher perception of effort. Thus, coaches should carefully choose the type of rewards when designing training tasks for youth basketball players.